Evaluation of the Mycoplasma genitalium Resistance Plus kit for the detection of M. genitalium and mutations associated with macrolide resistance. (3rd November 2017) - Pitt, Rachel; Cole, Michelle Jayne; Fifer, Helen; Woodford, Neil
Abstract : Objectives: To compare performance of the ResistancePlus kit (SpeeDx, Australia) with in-house methods for the detection of Mycoplasma genitalium- specific DNA and mutations associated with resistance to macrolide antimicrobials, directly from clinical specimens. Methods: Assay specificity and sensitivity was analysed using DNA from 46 non- M. genitalium organisms and standard curve analysis, respectively. A panel of archived DNA extracted from 97 M. genitalium -positive clinical specimens, for which the macrolide susceptibility genotype had been previously determined, were tested on the assay and results compared. Results: Final analytical specificity was 100%. Sensitivity was detected to at least 140 genome copies/µL. The assay detected M. genitalium in 92/97 (94.9%, 95% CI 88.4% to 98.3%) previously positive specimens. The genetic macrolide susceptibility assigned was concordant with previous results in 85/92 (92.4%, 95% CI 85.0% to 96.9%) specimens or 85/97 (87.6%, 95% CI: 79.4% to 93.4%) when the false-negative specimens were included. On seven (7/92, 7.6%) occasions, resistant specimens were called susceptible. Further testing resolved discrepancies for all but five (5.2%) specimens. Conclusions: The ResistancePlus assay generally performed well in comparison to methods currently employed at the reference laboratory. It detected a range of different mutations; however, a small number of specimens that were genotyped as macrolide resistant by Sanger sequencing were either not detected by the assay or were genotyped as susceptible. This could impact on treatment outcomes if assay results were used for patient management.